Finance policy of Soviet Union in occupied Lithuania in 1940-1990: myths and reality - Komičienė, Vida (Genocidas ir rezistencija, 2021)
The article analyses a relevant issue – the investigation prompted by public demand into the damage inflicted by the Soviet Union – which is important for Lithuania, Latvia and Estonia, as well as for foreign countries, because the economic development of the Baltic States was suspended during the long years of subjugation. Calculating the damage caused by the Soviet occupation is also important because Russian propaganda is constantly spreading the myth that Lithuania, like the other Baltic countries, benefited from Soviet rule to such an extent that it should pay for the factories they built, the socialist prosperity they created, etc. The aim is to use the financial documentary material – declassified financial accounting documents of the occupation regime – stored in the Lithuanian Central State Archive to establish the aspect of financial damage in order to clarify the myth of Lithuania’s alleged debt to the USSR.